2019
DOI: 10.1186/s40248-019-0197-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical course and management of idiopathic pulmonary fibrosis

Abstract: Idiopathic pulmonary fibrosis (IPF) is a progressive, fatal interstitial lung disease (ILD) with an unpredictable clinical course. Although IPF is rare, healthcare professionals should consider IPF as a potential cause of unexplained chronic dyspnea and/or cough in middle-aged/elderly patients and refer patients to a pulmonologist for evaluation. Making a diagnosis of IPF requires specialist expertise. Multidisciplinary discussion, involving at minimum a pulmonologist and a radiologist with expertise in the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 72 publications
0
17
0
Order By: Relevance
“…Idiopathic pulmonary fibrosis (IPF) is a rare chronic progressive disease of unknown etiology that affects both physical and emotional well-being [ 1 3 ]. It is characterized by irreversible loss of lung function due to fibrosis, which manifests as symptoms of increasing cough and dyspnea and impaired quality of life [ 2 6 ]. Lung transplantation is limited to a minority of patients and patients primarily rely on antifibrotic therapy plus several supportive/palliative treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Idiopathic pulmonary fibrosis (IPF) is a rare chronic progressive disease of unknown etiology that affects both physical and emotional well-being [ 1 3 ]. It is characterized by irreversible loss of lung function due to fibrosis, which manifests as symptoms of increasing cough and dyspnea and impaired quality of life [ 2 6 ]. Lung transplantation is limited to a minority of patients and patients primarily rely on antifibrotic therapy plus several supportive/palliative treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, RDNs can address nutrition issues while providing credible, evidence‐based recommendations to patients with ILD. Previous research has identified patient education, symptom relief, and management of comorbidities as vital components of supportive care in ILD management 90 . RDNs can support patients in each of these three supportive care components using their nutrition expertise and skills.…”
Section: Discussionmentioning
confidence: 99%
“…Adverse events are the most common reason for patients to discontinue medications 89 . In general, medication‐related gastrointestinal (GI) adverse events can be managed through dose adjustment, treatment interruption, and/or symptoms management 90 . Therefore, involvement of healthcare professionals to provide symptomatic and supportive care to patients in order to manage these medication‐related adverse events is an important component of ILD/IPF management.…”
Section: Other Nutrition Concernsmentioning
confidence: 99%
“…Nevertheless, diagnosis of IPF is complex and we did not tabulate multidisciplinary confirmation of IPF. 36 Secondly, we could not reliably stratify our study population based on the severity of IPF because of the complexities and controversies of ILD grading. 37 Although it has been shown that an absolute decline in FVC [ 10% or in DLCO [ 15% over a six-month time period is strongly associated with disease progression in non-surgical ILD patients, this study was inadequately powered to assess relationships between PFT values and postoperative outcomes.…”
Section: Discussionmentioning
confidence: 99%